2021
DOI: 10.1016/j.gfs.2021.100571
|View full text |Cite
|
Sign up to set email alerts
|

‘We would rather die from Covid-19 than from hunger’ - Exploring lockdown stringencies in five African countries

Abstract: Facing COVID-19, African countries were confronted with a dilemma: enacting strict lockdowns to “flatten the curve” could potentially have large effects on food security. Given this catch-22 situation, there was widespread concern that Africa would suffer most from the pandemic. Yet, emerging evidence in early 2021 showed that COVID-19 morbidity remained low, while “biblical famines” have been avoided so far. This paper explores how five African countries maneuvered around the potentially large trade-offs betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…For example, Rwanda and Vietnam have been rightly praised for exemplary containment of COVID-19 ( Karim et al, 2021 , Van Tan, 2021 ), but during the periods of stringent restrictions, we observed severe food insecurity outcomes. Media analysis from five African countries has shown that popular narratives often framed the situation as a balance between containment of the COVID-19 virus and food security; and that this was a hot topic in all five of the locations studied ( Birner et al, 2021 ). Policy responses often relaxed after complaints of food insecurity or economic hardship were received, and some measures were taken by governments which have not been captured by the data presented in this survey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Rwanda and Vietnam have been rightly praised for exemplary containment of COVID-19 ( Karim et al, 2021 , Van Tan, 2021 ), but during the periods of stringent restrictions, we observed severe food insecurity outcomes. Media analysis from five African countries has shown that popular narratives often framed the situation as a balance between containment of the COVID-19 virus and food security; and that this was a hot topic in all five of the locations studied ( Birner et al, 2021 ). Policy responses often relaxed after complaints of food insecurity or economic hardship were received, and some measures were taken by governments which have not been captured by the data presented in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the surveys reported here (conducted in the latter half of 2020) and various literature reporting other studies based on data from 2020, negative food security and economic outcomes were clearly evident amongst rural households, and many households dug into their reserves to buffer against income losses and food shortages. Media analysis ( Birner et al, 2021 ) shows that popular narratives in five African countries commonly framed a choice between exacerbating poverty and containing COVID-19, and that often the governments relaxed containment measures in acknowledgement of the economic hardships caused (Rwanda was an example of this). Going forward, we conclude that the careful monitoring of economic and food security implications of non-pharmaceutical interventions is needed in order to minimise undesirable outcomes for human welfare and development.…”
Section: Discussionmentioning
confidence: 99%
“…The agriculture and the commerce ministries had to implement measures to create market rebalancing as there was a likelihood of starvation or famine. 84 Due to the fear of famine, some of these African countries avoided strict and prolonged lockdown measures. This occurred partly because several of these African countries depended on imported goods.…”
Section: Historijski Pogledi 8 -Historical Viewsmentioning
confidence: 99%
“…In the COVID-19 pandemic, long-term and strict social blockade may result in some low-income people completely losing their financial savings. When this happens, they are more willing to break the blockade and go out to find jobs and food ( 58 ). Members of the disability group often have low incomes ( 59 ), meaning they will be more economically impacted by the pandemic.…”
Section: Provide Reasonable Financial Protection To People With Disabilities In the Pandemicmentioning
confidence: 99%